Increasing constraint of aridity on tree intrinsic water use efficiency - Mengjie Wang; Shushi Peng; Zihan Lu; Xiangtao Xu; Andrew Felton; Anping Chen (Nature Communications)
Abstract The intrinsic water use efficiency (W) of trees serves as a key variable linking water and carbon fluxes in forest ecosystems. Interannual variations in aridity (e.g., represented by the Standardized Precipitation Evapotranspiration Index, SPEI) can cause changes in W. However, it is unclear whether the aridity constraint on W, as indicated by the sensitivity of W to SPEI (S W ), has changed with recent climate change. Here, we use stable carbon isotope abundance of tree rings from 296 sites to estimate interannual variation of W and S W . S W is defined as the slope in a linear regression of W against SPEI and is negative for most of the tree sites. Our findings suggest an increasing aridity constraint on W from 1951 to 2010, with the absolute value of S W increasing by 112% over the period. This more negative trend in S W is statistically significant for gymnosperms but not for angiosperms. The change in S W over the past six decades is linked to rising aridity and atmospheric CO2, as revealed by a theoretical stomatal model. Our study highlights the increasing aridity control on tree W variation and implies the resilience of tree intrinsic functions to aridity variability under future climate change.